Slit-lamp based assessment of peripheral versus central regions of the human corneal endothelium. Issue 2 (April 2020) - Tavazzi, Silvia; Cozza, Federica; Colciago, Sara; Zeri, Fabrizio
Highlights: A slit-lamp allows to compare the morphometric properties of corneal endothelium in central and extreme peripheral areas. In young healthy non-CL wearers, the periphery shows higher hexagonality and lower coefficient of variation than the centre. Hexagonality and coefficient of variation do not depend on possible experimental artefacts related to image magnification. A clinical evaluation of the corneal endothelium requires a full characterization of the different areas. Data could be explained by a possible regenerative capacity of peripheral endothelial cells, as reported in the literature. Abstract: Purpose: : To compare the central and peripheral (< 2 mm from the limbus) endothelial regions of the human cornea of young contact lens (CL) neophytes, in terms of endothelial cell density (ECD), polymorphism through cell hexagonality (HEX), and polymegethism through the coefficient of variation of cell areas (CoV). Materials and methods: : In vivo, central, temporal, and nasal ECDs, HEXs, and CoVs were determined for thirty healthy right eyes (age: 22–30 years) using a Takagi 700 G L LED slit-lamp biomicroscope equipped with the centre-dot EndoKer© for the analysis of endothelium images. Results: : The mean central ECD (2586 ± 233 mm −2 ) was lower than peripheral ECDs (nasal 2733 ± 225 mm −2, temporal 2674 ± 260 mm −2 ) (p = 0.03 and p = 0.02, respectively). The mean central HEX (53.0 ± 4.6%) was lower than peripheral HEXs (nasal 57.2 ± 4.3%, temporal 57.1 ± 4.5%) (both p < 0.005), while the mean central CoV (28.2 ± 2.5%) was higher than peripheral CoVs (nasal 25.8 ± 2.2%, temporal 26.1 ± 2.2%) (both p ≤ 0.001). Conclusions: : In young healthy non-CL wearers, the peripheral corneal endothelium displays a higher ECD and significantly better cell regularity (higher HEX and lower CoV) compared to the central cornea. A clinical evaluation of the corneal endothelium requires, therefore, a full characterization of the different areas.